Characterizing and modeling the efficiency limits in large-scale production of hyperpolarized (129)Xe - Freeman, M.S. (Phys Rev A, 2014)
The ability to produce liter volumes of highly spin-polarized (129)Xe enables a wide range of investigations, most notably in the fields of materials science and biomedical MRI. However, for nearly all polarizers built to date, both peak (129)Xe polarization and the rate at which it is produced fall far below those predicted by the standard model of Rb metal vapor, spin-exchange optical pumping (SEOP). In this work, we comprehensively characterized a high-volume, flow-through (129)Xe polarizer using three different SEOP cells with internal volumes of 100, 200 and 300 cc and two types of optical sources: a broad-spectrum 111-W laser (FWHM = 1.92 nm) and a line-narrowed 71-W laser (FWHM = 0.39 nm). By measuring (129)Xe polarization as a function of gas flow rate, we extracted peak polarization and polarization production rate across a wide range of laser absorption levels. Peak polarization for all cells consistently remained a factor of 2-3 times lower than predicted at all absorption levels. Moreover, although production rates increased with laser absorption, they did so much more slowly than predicted by the standard theoretical model and basic spin exchange efficiency arguments. Underperformance was most notable in the smallest optical cells. We propose that all these systematic deviations from theory can be explained by invoking the presence of paramagnetic Rb clusters within the vapor. Cluster formation within saturated alkali vapors is well established and their interaction with resonant laser light was recently shown to create plasma-like conditions. Such cluster systems cause both Rb and (129)Xe depolarization, as well as excess photon scattering. These effects were incorporated into the SEOP model by assuming that clusters are activated in proportion to excited-state Rb number density and by further estimating physically reasonable values for the nanocluster-induced, velocity-averaged spin-destruction cross-section for Rb (<σ(cluster-Rb)v> ≈4×10(-7) cm(3)s(-1)), (129)Xe relaxation cross-section (<σ(cluster-Xe)v> ≈ 4×10(-13) cm(3)s(-1)), and a non-wavelength-specific, photon-scattering cross-section (σ(cluster) ≈ 1×10(-12) cm(2)). The resulting modified SEOP model now closely matches experimental observations.